2014
DOI: 10.1371/journal.pone.0086941
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Followed by Surgery versus Surgery Alone for Gastric Carcinoma: Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundThe effect of neoadjuvant chemotherapy (NAC) on Gastric carcinoma (GC) has been extensively studied, while its survival and surgical benefits remain controversial. This study aims to perform a meta-analysis of high-quality randomized controlled trials (RCTs), comparing efficacy, safety and other outcomes of NAC followed by surgery with surgery alone (SA) for GC.MethodsWe systematically searched databases of MEDLINE, EMBASE, The Cochrane Library and Springer for RCTs comparing NAC with SA when treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 76 publications
1
48
1
3
Order By: Relevance
“…A recent meta-analysis and a systematic review of NAC followed by surgery versus surgery alone were comprised of mostly small, single center trials with similarly limited proportions of T2N0 disease. 8,9 Contrary to the landmark trials, these pooled analyses did not show a benefit of NAC prior to surgery compared to surgery alone. However, other systemic reviews have shown an OS benefit for NAC.…”
contrasting
confidence: 66%
“…A recent meta-analysis and a systematic review of NAC followed by surgery versus surgery alone were comprised of mostly small, single center trials with similarly limited proportions of T2N0 disease. 8,9 Contrary to the landmark trials, these pooled analyses did not show a benefit of NAC prior to surgery compared to surgery alone. However, other systemic reviews have shown an OS benefit for NAC.…”
contrasting
confidence: 66%
“…Previous studies have established a key role of H. pylori in the pathogenesis of a variety of gastric diseases including gastritis, peptic ulcers, B lymphoma, and gastric cancer. [1][2][3][4]7,8 The impaired balance between H. pylori-producing aggressive bacterial endotoxins and host defensive mechanisms is critical in the different clinical outcomes observed in patients infected with this bug. Recently, we have reported that gastric fibroblasts can represent cellular target of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some patients lose the opportunity of curative resection resulting from the aggressive nature of GC. Although chemoradiotherapy and targeted therapy have confirmed an improvement in host response rates, the cancer recurrences and metastases are frequently observed 2, 3, 4, 5, 6. The bacteria Helicobacter pylori ( H. pylori) is one of the major risk factors for GC development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations